1988
DOI: 10.1159/000120366
|View full text |Cite
|
Sign up to set email alerts
|

Parietal Cephaloceles: Radiographic and Magnetic Resonance Imaging Evaluation

Abstract: Three patients with parietal cephaloceles underwent evaluation and treatment at Duke University Medical Center between 1984 and 1987. All presented within the first 2 years of life with painful swelling near the vertex of the head. All patients had skull films and computed tomography, and two underwent magnetic resonance imaging (MRI). All 3 children had associated hindbrain deformities; two with Dandy-Walker malformation, the third with a Chiari II malformation. Each child eventually developed hydrocephalus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The association with these malformations is not unexpected, due to various pathophysiological events leading to cephalocele. The previously reported CNS anomalies include: dysgenesis of the corpus callosum, formation of interhemispheric fissure, split superior sagittal sinus, absence of falx cerebri and dysgenesis of the tentorium [17,18,19]. Mahapatra and Agrawal [20] reported that corpus callosum agenesis is seen in 7% of children with anterior encephaloceles in a series of 103 cases aged over 32 years.…”
Section: Discussionmentioning
confidence: 99%
“…The association with these malformations is not unexpected, due to various pathophysiological events leading to cephalocele. The previously reported CNS anomalies include: dysgenesis of the corpus callosum, formation of interhemispheric fissure, split superior sagittal sinus, absence of falx cerebri and dysgenesis of the tentorium [17,18,19]. Mahapatra and Agrawal [20] reported that corpus callosum agenesis is seen in 7% of children with anterior encephaloceles in a series of 103 cases aged over 32 years.…”
Section: Discussionmentioning
confidence: 99%
“…Less common sites include the frontal region where the encephalocele may protrude into the nasal cavity. Least common lesion sites include the temporal and parietal region (46). The neural tissue in an encephalocele usually connects to the underlying central nervous system through a narrow neck of tissue.…”
mentioning
confidence: 99%
“…11,13,22 Interestingly, venous involvement in patients with parietal encephaloceles has been reported occasionally. 5,7,15,17,19 In this article we describe an unusual case of congenital extracranial teratoma coexisting with an IPE, in which a persistent primitive falcine vein and a bifid sagittal sinus were demonstrated on MR venography. 5,7,15,17,19 In this article we describe an unusual case of congenital extracranial teratoma coexisting with an IPE, in which a persistent primitive falcine vein and a bifid sagittal sinus were demonstrated on MR venography.…”
mentioning
confidence: 96%